The Socialization of a Novice Teacher of English: Becoming an Agent of Change - Claudia Patricia Mesa Villa (Asociación Colombiana de Profesores de Ingles, 2017)
This case study reports the analysis of the induction as a socialization process of a Colombian novice teacher of English. Since critical approaches to socialization highlight the role of novice teachers in critical school transformation during their induction stage, this study aims to disclose the teacher's possibilities of becoming an agent of change. The data collection procedures included interviews, class observations and document analysis. The findings revealed that the teacher's socialization was not a gradual transition and his possibilities to contribute to school transformation differed in accordance with the interplay among his professional interests and school factors.